The interaction of approach-alcohol action tendencies, working memory capacity, and current task goals predicts the inability to regulate drinking behavior - Sharbanee, Jason; Stritzke, W.; Wiers, R.; Young, P.; Rinck, M.; MacLeod, C. (2013)
The inability to regulate alcohol consumption has been attributed to an imbalance between stimulus-driven behavioral biases, or action tendencies, and the ability to exert goal-directed control, or working memory capacity (WMC). Previous research assessing the interaction between these variables has not considered the effect of whether individuals' current goals or task demands require goal-directed control. Our aim was to examine the potential interaction of appetitive action tendencies and the ability to exert control over these action tendencies as a function of whether task demands require applying control for successful task completion. Two groups of social drinkers (n = 40 per group) who differed in their ability to regulate their alcohol consumption completed a novel variant of the Approach-Avoidance Task (AAT), which separately assessed approach and avoid trials. The approach and avoidance responses differentially require goal-directed control, depending on whether the task-relevant response is incongruent with the stimulus-driven action tendency. Results indicated that (a) group differences in AAT indices were only observed on trials that required an avoidance movement, which are trials where the task-relevant response would be incongruent with an approach action tendency, and (b) the extent of the group differences for these avoidance trials was moderated by individual differences in WMC, such that problem drinkers with lower WMC showed greater behavioral bias toward alcohol than those with higher WMC. These findings suggest that difficulties in regulating alcohol consumption arise from a complex interaction of action-tendencies, WMC, and current goals or task demands.